Optical Wireless Communications An Emerging Technology - Uysal, Murat; Capsoni, Carlo; Ghassemlooy, Zabih; Boucouvalas, Anthony; Udvary, Eszter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on optical wireless communications (OWC), an emerging technology with huge potential for the provision of pervasive and reliable next-generation communications networks. It shows how the development of novel and efficient wireless technologies can contribute to a range of transmission links essential for the heterogeneous networks of the future to support various communications services and traffic patterns with ever-increasing demands for higher data-transfer rates. The book starts with a chapter reviewing the OWC field, which explains different sub-technologies (visible-light, ultraviolet (UV) and infrared (IR) communications) and introduces the spectrum of application areas (indoor, vehicular, terrestrial, underwater, intersatellite, deep space, etc.). This provides readers with the necessary background information to understand the specialist material in the main body of the book, which is in four parts. The first of these deals with propagation modelling and channel characterization of OWC channels at different spectral bands and with different applications. The second starts by providing a unified information-theoretic treatment of OWC and then discusses advanced physical-layer methodologies (including, but not limited to: advanced coding, modulation diversity, cooperation and multi-carrier techniques) and the ultimate limitations imposed by practical constraints. On top of the physical layer come the upper-layer protocols and cross-layer designs that are the subject of the third part of the book. The last part of the book features a chapter-by-chapter assessment of selected OWC applications. Optical Wireless Communications is a valuable reference guide for academic researchers and practitioners concerned with the future development of the world's communication networks. It succinctly but comprehensively presents the latest advances in the field.
Part I: Outlook -- An Overview of Optical Wireless Communications -- Part II: Channel Modelling and Characterization -- Optical Propagation in Unguided Media -- Meteorological Effects on Free-Space Optical Links -- Experimental Validation of FSO Channel Models -- Channel Modeling for Satellite-to-Ground Links -- Visible-Light Channel Modeling and Characterization -- Ultraviolet Scattering Communication Channels -- Part III: Physical Layer Design Issues -- Information Theoretical Characterization of FSO Links -- Diversity Techniques for Mitigating Channel Effects in FSO Links -- MIMO Optical Wireless Communication Systems -- Cooperative Free-Space Optical Networks -- Cooperative Visible-Light Communications -- OFDM-Based Visible-Light Communications -- Frequency Domain Equalization for VLC -- Coherent FSO Communications -- Part IV: Upper Layer Domains -- Multiple Access in Visible-Light Communication Networks -- Link Layer Protocols for Short-Range IR Communications -- Scheduling Protocols in FSO Networks.-FSO Network Design for Resilient Cellular Backhauling -- Part V: Implementation Aspects and Emerging Applications -- Overview of OWC Testbeds and an Open-Source FSO Link Design VLC-Based Indoor Localization -- Vehicular Visible-Light Communications -- Camera Communications -- Optical Wireless Body Area Networks for Healthcare Applications -- Ultraviolet Communications for Sensor Networks -- Free-space Quantum Key Distribution.
Keywords: Telecommunication; Lasers; Communications Engineering, Networks; Laser; Microwaves, RF Engineering and Optical Communications